2010
DOI: 10.1016/j.bcp.2009.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes in the damaged brain: Molecular and cellular insights into their reactive response and healing potential

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. A c c e p t e d M a n u s c r i p t 1 2 3 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
266
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 288 publications
(277 citation statements)
references
References 167 publications
(230 reference statements)
9
266
0
2
Order By: Relevance
“…The astrocytes used in our study are non-proliferating TD cells, thus reproducing the state of the overwhelming majority of adult brain astrocytes. 25 Deficits in this key feature are the likely reason for a certain degree of DDR activation observed in proliferating astrocytic lines 26,27 and differentiated astrocytes displaying residual proliferation. 28 Importantly, downregulation of DDR is peculiar of astrocytes and is not necessarily associated with terminal differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The astrocytes used in our study are non-proliferating TD cells, thus reproducing the state of the overwhelming majority of adult brain astrocytes. 25 Deficits in this key feature are the likely reason for a certain degree of DDR activation observed in proliferating astrocytic lines 26,27 and differentiated astrocytes displaying residual proliferation. 28 Importantly, downregulation of DDR is peculiar of astrocytes and is not necessarily associated with terminal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…30 In neurons, p53-dependent cell death upon genotoxic stress was also reported, and sometimes associated with their re-entry into cell cycle, 31,32 whereas in vivo astrocytes are only known to re-enter cell cycle under pathological condition of reactive gliosis. 25 In this respect in would be interesting to check whether DDR and apoptosis proficiency of brain astrocytes increase when they undergo injury-induced reactive gliosis. It is therefore possible that different TD cell types are differently radiosensitive, depending on their specific role and physiological context.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic changes to astrocyte-neuron interaction mediated by changes to distal astrocytic processes are known to influence neuron-astrocyte plasticity (15). Although astrocytes are generally stationary cells that provide a supportive network for neuronal cells and synapses, migratory and proliferating astrocytes have been observed in glial scarring, an environment with diminished neuronal function (43,44). In this study, an altered cellular environment in the form of nanotopography was shown to affect astrocyte biophysical attributes (shape and roughness) so as to alter their interaction with neurons.…”
Section: Regions Of Amyloid Plaque Buildup In Alzheimer's Present Incmentioning
confidence: 99%
“…Cortical brain astrocytes express the full complement of P2Y and P2X receptors, with significant changes in the expression level following traumatic or ischemic events [76]. The purinergic system is directly involved in modulating reactive astrogliosis and astrocyte secretion of cytokines and chemokines in the brain cortex [76].…”
Section: Spinal Cord Microglia and Astrocytesmentioning
confidence: 99%